Green Accounting Penerapan Green Accounting, Corporate Social Responsibility, dan Ukuran Perusahaan Terhadap Profitabilitas - tiara sundari; Virna Sulfitri (LPPM Universitas Ibnu Sina, 2022)
This study uses a quantitative methodology. The purpose of this study is to test and analye the application of green accounting, CSR, and firm size to manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. Green Accounting is proxied through environmental performance. Profitability is quantifed using NPM. There are 836 manufacturing companies listed on the IDX listing, but only 19 manufacturing companies are consistent from 2016-2020 according to the research criteria. So that the sampleof this research is counted for 5 years as many as 95. Companies thar are included in the researcg sample are companies thar are PROPER participants in the Ministry of Environment Program of the Republic of Indonesia from 2016-2020. This research utilizes secondary data, in the form of annual reports, financial reports, and compay sustainability reports which can be obtained on the website www.idx.ci.id and the official website of manufacturing companies. The data analysis method uses is descriptive statictical data analysis, classical assumption test, and multiple regression analysis. The research findings show that environmental performance has no effect on profitability because the significant value is > 0.05. Meanwhile, CSR has a significant positive effect on profitability because the significant value is less than 0.05 and the beta coefficient has a positive direction, and firm size has a significant negative effect on profitability because the significant value is < 0.05 but the beta coefficient has a negative direction.